1982
DOI: 10.1128/iai.36.1.30-37.1982
|View full text |Cite
|
Sign up to set email alerts
|

Human serum antibodies to varicella-zoster virus thymidine kinase

Abstract: The conditions required for the production of varicella-zoster virus (VSV)-induced deoxythymidine kinase (dTk) have been studied. Extracts from Vero cells harvested 62 h after VZV infection were found to contain VZV-induced dTk activity, with a minimal contribution from the cellular dTk activity. VZV dTK was shown to have a broad substrate specificity phosphorylating both deoxythymidine, deoxycytidine, and iododeoxyuridine. Deoxythymidine triphosphate inhibition studies revealed an intermediate deoxythymidine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
8
0

Year Published

1983
1983
1989
1989

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…We have previously described a sensitive TK assay and its potential use in clinical virology (Gronowitz and Kallander, 1980). The sensitivity of the TK assay and the fact that antisera exist which neutralize HSV TK in a types-specific manner makes it moreover possible to use a TK inhibition assay for direct typing of HSV isolates and vesicle fluid specimens (Gronowitz et al, 1982). In the present communication we describe an improved TK assay, applicable to the detection of TK activity in human serum, and the results indicate that s-TK may serve as avaluable marker in clinical medicine.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We have previously described a sensitive TK assay and its potential use in clinical virology (Gronowitz and Kallander, 1980). The sensitivity of the TK assay and the fact that antisera exist which neutralize HSV TK in a types-specific manner makes it moreover possible to use a TK inhibition assay for direct typing of HSV isolates and vesicle fluid specimens (Gronowitz et al, 1982). In the present communication we describe an improved TK assay, applicable to the detection of TK activity in human serum, and the results indicate that s-TK may serve as avaluable marker in clinical medicine.…”
Section: Discussionsupporting
confidence: 84%
“…These values are in the same range as those previously reported for the purified human TK1 isozyme (dThd 2.6 X 10" M, IdUrd 2.4 X 10" M; Lee and Cheng, 1976). For the human TK2, the re orted IdUrd (Lee and Cheng, 1976) while the HSV TKs have K, values in the range 1.9-2.8 X lo-' for IdUrd and 4.6-6.6XlO-' for dThd (Gronowitz and Kallander, 1980) Our previously described assay has been used for detection of minute amounts of viral TK enzyme in specimens from patients with HSV infections (Gronowitz et al, 1982) and was also used for the detection of antibodies against HSV and varicella-zoster virus (VZV) TK in human serum (Gronowitz and Kailander, 1981;Kallander et al, 1982). When performing these antibody studies we found that a few sera, derived from patients with infectious mononucleosis (IM), contained high levels of TK activity.…”
mentioning
confidence: 99%
“…While accurate diagnosis and/or efficient chemotherapy methods were developing from the immunological and functional specificities of DNase and thymidine kinase (TK) activities induced by several human herpes viruses (Cheng et al, 1978(Cheng et al, , 1982Gronowitz et al, 1982;Kallander et al, 1982). we reached agreement with other authors on the existence of EBV-specific DNase (Tan et al, 19826;Ooka et al, 1984) and TK (Ooka ef al.. 1983;McGabhann er al., 1984;Littler et al, 1986Littler et al, , 1987de Turenne-Tessier er al., 1986).…”
supporting
confidence: 85%
“…HSV dTk's are immunogenic, and antisera against the isozymes have been obtained by immunization of animals with extracts from infected or transformed cells (2,9,14). Antibodies against both HSV and VZV dTk are also present in human sera after viral infections (3,6,10). We have shown in a separate study that the dTk level in human serum in connection with infectious mononucleosis is elevated 10 to 40 times.…”
mentioning
confidence: 92%
“…The assay measures residual enzyme activity after preincubation of vesicle fluid with HSV type 1 (HSV 1) or HSV type 2 (HSV 2) dTk antisera. Further studies of VZV dTk in infected cell cultures indicated high levels of enzyme activity (10). This prompted us to attempt direct detection of VZV dTk in clinical specimens to develop a general rapid typing method for VZV, HSV 1, and HSV 2 infections.…”
mentioning
confidence: 99%